Changes of high altitude glaciers from 1969 to 2010 in the Trans-Himalayan Kang Yatze Massif, Ladakh, Northwest India - Schmidt, Susanne; Nüsser, Marcus (Arctic, antarctic, and alpine research, 2012)
This study reports changes of small glaciers in the Trans-Himalayan Kang Yatze Massif, Ladakh, northwest India, between 1969 and 2010. The region covers an area of about 1000 km2 and is located in a transitional position between predominantly receding glaciers of the Central Himalaya and some advancing ice masses of the Karakorum. A multi-temporal remote sensing approach based on satellite images (Corona, SPOT, Landsat) was used to detect and analyze area changes of 121 small glaciers and to measure the retreat of 60 cirque and valley glaciers between 1969 and 2010. Over the last four decades, the glaciated area decreased by about 14% (0.3% yr−1) from 96.4 to 82.6 km2 and the average ice front retreat amounts to 125 m (3 m yr−1). The ice cover loss shows a high decadal variability with the maximum shrinkage between 1991 and 2002 (0.6% yr−1), followed by a lower decrease rate since then (0.2% yr−1). Due to the high variability of glacier change with a generally decreasing trend and a few stable glaciers, it becomes obvious that an extrapolation even on a regional scale is problematic. Therefore, a consideration of differing responses of various glacier types and glacier sizes is of utmost importance.